Contextual Clues Effect on Students Reading Comprehension Using The Wonderful Wizard of Oz Novel - Yeni Mardiyana Devanti; Agryanda Agryanda; Indri Astutik (Universitas Muhammadiyah Jember, 2022)
The research was pre-experimental research and it was conducted by using one group pre-test post-test design. The subject was the fourth year students of English Language Education Program consisting of 33 students. The text used during the treatment was The Wonderful Wizard of Oz Novel by L. Frank Baum published by World Public Library. It consists of 214 pages but only some parts of the novel that was used during the treatment. The data collected using both of the test above, and the instrument used was a reading comprehension test about The Wonderful Wizard of Oz Novel. The test consists of 20 questions in multiple choices form. T-test was used in order to analyze the data. It was found that the result before and after the treatment were very much different. The t-test score is -6.875 and the t-table is 2.997 in the level of significant 5%. In the t-test the plus and minus signs are not considered so that the value of -6.857 2.997 (ttable). Therefore, the final conclusion can be stated as that there was a significant effect of contextual clues on students’ reading comprehension using The Wonderful Wizard of Oz Novel.